2017
DOI: 10.14735/amko20172s13
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsies – the Clinics and the Molecules

Abstract: Unlike bone marrow biopsies, liquid biopsies represent a gentler, more accessible, less painful, repeatable and more comprehensive approach to get biologically relevant information about the entire tumor but also about treatment response and level of minimal residual disease. This is all possible since peripheral blood contains not only circulating tumor cells but also many circulating molecules of nucleic acids (microRNA, cell-free DNA, long non-coding RNA etc.). Multiple myeloma is a genetically heterogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The invasive biopsy may be occasionally unsuccessful in the first attempt, necessitating additional biopsies; second, a biopsy specimen is only representative of a small proportion of the malignancy and might not represent the overall status of the malignancy due to its heterogeneity. 5 Thus, identification of noninvasive methods for the detection of CAs in patients with MM has become an area of intense research interest because of the limitations of traditional methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The invasive biopsy may be occasionally unsuccessful in the first attempt, necessitating additional biopsies; second, a biopsy specimen is only representative of a small proportion of the malignancy and might not represent the overall status of the malignancy due to its heterogeneity. 5 Thus, identification of noninvasive methods for the detection of CAs in patients with MM has become an area of intense research interest because of the limitations of traditional methods.…”
mentioning
confidence: 99%
“…However, current cytogenetic examinations including the recommended method for detection of HRC—fluorescent in situ hybridization (FISH)—are associated with the common issues encountered with all other procedures that require biopsy. The invasive biopsy may be occasionally unsuccessful in the first attempt, necessitating additional biopsies; second, a biopsy specimen is only representative of a small proportion of the malignancy and might not represent the overall status of the malignancy due to its heterogeneity 5 . Thus, identification of noninvasive methods for the detection of CAs in patients with MM has become an area of intense research interest because of the limitations of traditional methods.…”
mentioning
confidence: 99%
“…It is possible that the biopsy plug simply secretes substances, such as neurotransmitters, onto the hiPSC-derived cortical neuron cell layer, which could result in network activity in the read-out layer capturing the pro-convulsive electrophysiological phenotype. It was previously shown that a freshly operated brain biopsy may slowly release compounds, such as microRNAs [38], which can leak onto the hiPSC-derived neuronal cell layer and change its response over time. Future studies on elaborating the origin of the electrophysiologic activity may address the connectivity between the neuronal cell layer and the biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Our attention is currently focused on liquid bio psies, meaning samples of PB. Both research teams in Ostrava and Brno have contributed to this Supplementum by several articles [15][16][17].…”
Section: Peripheral Bloodmentioning
confidence: 99%